Answer:
x=1, y=7
Step-by-step explanation:
y = -3x + 10 - first equation
y=-3x + 4 - second equation
rearrange the expression to
-3x-y= -10
3x-y= -4
pick an equation and simplify; lets pick the second equation
3x-y= -4
divide 3 by both sides
x= - third equation
substitute the value of x into an equation; lets pick the first equation
-3x-y= -10
-3- y = -10
simplify. -3 cancels 3 so we are left with
-1(-4+y)-y = -10
simplify
4-y-y= -10
4-2y= -10
subtract 4 from both sides
-2y= -10-4
-2y= -14
divide -2 by both sides
y=7
substitute the value of y, (y=7) in an equation, we are using the second equation
3x-y= -4
3x-7= -4
3x = -4+7
3x= 3
divide 3 by both sides
x=1
so the answer is x=1, y=7
Answer:
y=4
Step-by-step explanation:
4y + 3 =19
4y = 16
y= 4
A constant can either shift the graph up or down. If coefficient is less than 1 it will make the graph wider, if it's more than 1 it will make graph more narrow
Answer
The vertex is at point (-3, -1)
The axis of symmetry is x = -3
Explanation
We are asked to find the vertex and axis of symmetry of the equation given.
f(x) = x² + 6x + 8
The vertex of a quadratic equation is the point where the graph of the quadratic equation changes from sloping negatively to sloping positively and vice-versa.
The axis of symmetry represents the straight line that divides the graph of the quadratic equation into two mirror parts that are similar to and are mirror images of each other. This axis of symmetry usually passes through the vertex.
To find the vertex, it is usually at the turning point where the first derivative of the quadratic equation is equal to 0.
(df/dx) = 0
f(x) = x² + 6x + 8
(df/dx) = 2x + 6
At the vertex
(df/dx) = 2x + 6 = 0
2x = -6
Divide both sides by 2
(2x/2) = (-6/2)
x = -3
We then insert this into the equation to get the corresponding f(x) value.
f(x) = x² + 6x + 8
f(-3) = (-3)² + 6(-3) + 8
= 9 - 18 + 8
= -1
Hence, the vertex is at point (-3, -1)
And since the axis of symmetry has to pass through the vertex,
The axis of symmetry is x = -3
Hope this Helps!!!